Microstrip array antenna with inset-fed for WLAN application - Norfishah Ab Wahab; W. Nor Syafizan W. Muhamad; Zuhani Ismail Khan; Suzi Seroja Sarnin (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper proposed three designs of microstrip array patch antennas, to resonate at 2.4 GHz. The purpose of the study is to achieve size reduction with acceptable performance for wireless communication system applications. Based on the array concept, the array antennas are arranged using corporate network technique. It is found that the simulated 4x3 patch array antenna achieved the compact size with dimension reduced up to 26% compared to 4x1 and 4x2 array patch antennas. In terms of return loss, the antenna attenuated more than 19 dB. The 4x3 patch array antenna is fabricated and measured using RO4350 microstrip substrate to validate the concept. The responses are found in good agreement between simulation and measurement.